Оптимізація виробничої програми в системі менеджменту аграрних підприємств - Горобець, Наталія Миколаївна; Gorobets, Natalya; Чорна, Інна Анатоліївна; Chorna, Inna (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2019)
Статтю присвячено розгляду загальних аспектів розробки оптимізаційної економіко-математичної моделі виробничих ресурсів сільськогосподарських підприємств. Виявлено резерви виробничого потенціалу, раціонального використання сівозмін та підвищення економічної ефективності господарської діяльності агропідприємства. Досліджено характерні умови та чинники, які потрібно враховувати в процесі розробки виробничої програми. Встановлено, що підвищення рівня дохідності агровиробників забезпечується за рахунок оптимізації їх виробничої структури на підставі результатів економіко-математичного моделювання. Обґрунтовано доцільність прийняття подальших управлінських рішень щодо їх економічного розвитку та підвищення конкурентоспроможності сільськогосподарської продукції на ринку. За результатами оптимізації виробничої структури передбачається збільшення обсягів виробництва продукції рослинництва і зростання виручки від реалізації продукції. Запропоновано системний підхід щодо планування обсягів посівних площ сільськогосподарських культур. Встановлено оптимальне співвідношення посівних площ, що дозволить збільшити обсяги виробництва сільськогосподарського підприємства. The article is devoted to the consideration of general aspects of the development of an optimization economic-mathematical model of agricultural resources of agricultural enterprises. Reserves of productive potential, rational use of crop rotation and increase of economic efficiency of economic activity of agro enterprises are revealed. The characteristic conditions and factors that need to be taken into account in the development of a production program are investigated. Applied testing of mathematical calculations has been carried out for an agricultural enterprise that wants to optimize its production structure in order to ensure maximum overall profitability. Such a model can be used to analyze and identify the reserves of resource potential of enterprises of any form of ownership, for different periods of time, as well as to identify the features of strategies for increasing the economic efficiency of economic activity, not only the enterprise as a whole, but also its individual units. In addition, the constructed model can be modified both structurally and substantively. The developed of economic-mathematical model provided for the main types of activities, in particular, the crop industry, namely, the cultivation of cereals and oilseeds. It was established that increasing the profitability of agricultural producers is ensured by optimizing their production structure based on the results of economic and mathematical modeling. The expediency of making further management decisions concerning their economic development and increase of competitiveness of agricultural products on the market is substantiated. According to the results of optimization of the production structure, it is expected to increase the volumes of crop production and increase the proceeds from sales of products. A systematic approach to planning the volumes of crop area of agricultural crops is proposed. The optimal correlation of sown area is established, which will allow to increase the volume of agricultural enterprise production. It has been proved that the process of modeling in the activity of agricultural enterprises enables to make optimal and effective management decisions at different stages of operation and development of the enterprise.
Оptimization of the manufacturing program in management system of agricultural enterprises
ORCID ID: 0000L0001L5032L2903 Н. М. Горобець ; ORCID ID: 0000L0003L3811L9069 І. А. Чорна
Keywords: виробничий менеджмент; production management; виробнича програма; production program; економіко-математична модель; economic-mathematical model; оптимізація; optimization; сільськогосподарське підприємство; agricultural enterprise